Effects of water levels on plant traits and nitrogen use efficiency in monoculture and intercropped artificial grasslands - Wan, Zhiqiang; Gu, Rui; Yan, Yulong; Bai, Lijun; Bao, Tiejun; Yang, Jie; Gao, Qingzhu; Ganjurjav, Hasbagan; Hu, Guozheng; Zhou, Haijun; Chun, Xi (Frontiers in Plant Science, 2022)
Water availability is a main factor affecting forage productivity of artificial grasslands, especially in a semi-arid region. Generally, intercropping of gramineous grass and leguminous grass can achieve high productivity. However, how different water availability affect the productivity of intercropping system is remained unclear. Here, we conducted a three year (2015-2017) manipulative water change (CK equivalent to the annual precipitation, +50% treatment equivalent to 50% increase over the average precipitation, -50% treatment equivalent to 50% decrease average precipitation) experiment to explore the responses of plant traits, nitrogen use efficiency and biomass of the monoculture Medicago sativa (a leguminous grass, M.s), monoculture Elymus nutans (a gramineous grass, E.n) and intercropping of M.s and E.n in a semi-arid region in Inner Mongolia, China. The results showed that biomass of the intercropping of M.s and E.n decreased 24.4% in -50% treatment compared to the CK, while the monoculture M.s decreased 34.4% under the -50% treatment compared to the CK. However, the biomass of them did not significantly differ from each other under +50% treatment. Compared to monoculture, M.s can obtain more nitrogen by biological nitrogen fixation and decrease the proportion of nitrogen absorbed from soils under intercropping in the same water conditions. Under intercropping, the proportions of nitrogen absorbed from soils by M.s were 87.4%, 85.1 and 76.9%, respectively in -50%, CK and +50% treatments. Under monoculture, these proportions were 91.9%, 89.3% and 82.3%, respectively in -50%, CK and +50% treatments. Plant trait, not soil nitrogen content was the main regulator for the productivity responses to water level changes. Our results highlight that intercropping can achieve higher productivity in both dry and wet conditions. Therefore, considering the fluctuating rainfall events in the future, it might be useful to alter the proportions of intercropped forage species in an artificial grassland to obtain optimal productivity by reducing the limitations of nitrogen availability. However, the economic viability of intercropping M. sativa and E. nutans should be evaluated in the future.